THE CAPITALIZATION OF EDUCATION IN A PSYCHOLOGICAL AND ISLAMIC PERSPECTIVE - Umami, Kartika Nur; Muhid, Abdul (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Capitalism that penetrated into the world of Education has changed the perspective of society about the purpose of education. Education has received results to obtain results using diplomas that have been obtained with a compilation obtained from educational institutions. Educational capitalism has also given a partition to the people who have low economics in education, which is for the poor who deserves education to be obtained. It is hoped that for people who have adequate education will be easily obtained. This article discusses educational capitalism with a psychological and Islamic perspective. Using the literature review method. The findings in this article indicate that education has reduced the true educational goals. Namely the process of actualizing all the potentials of themselves as God's creatures who are equipped by reason and potential.